Micromachined Wideband Ridge Gap Waveguide Power Divider at 220–325 GHz - Sadia Farjana; Ashraf Uz Zaman; Per Lundgren; Peter Enoksson (IEEE Access, 2022)
A micromachined ridge gap waveguide power divider operating at 220–325 GHz is presented. The device is fabricated by SUEX dry film photoresist. Dry film photoresist can be used to obtain geometrical features with high accuracy using a robust fabrication process. The designed power divider has simple geometrical features and a wide band performance. The measured transmission coefficients are equal to −3.5 ± 0.4 dB at 220–325 GHz and the measured input reflection coefficient is below −12 dB at 220–325 GHz. The measurement results are in good agreement with simulations, demonstrating that the proposed fabrication method is suitable for the fabrication of waveguide components operating at the millimeter and sub-millimeter wave range. The presented low-loss ridge gap waveguide power divider may enable cost-effective and rapid fabrication of passive devices such as high gain antennas operating up to THz frequencies.